Hijacking of the nervous system in cancer: mechanism and therapeutic targets - Yu Zhang; Qili Liao; Xuyang Wen; Jiayan Fan; Tifei Yuan; Xuemei Tong; Renbing Jia; Peiwei Chai; Xianqun Fan (Molecular Cancer)
Abstract The activity of neurons in the vicinity of tumors is linked to a spectrum of cellular mechanisms, including the facilitation of tumor cell proliferation, synapse formation, angiogenesis, and macrophage polarization. This review consolidates the current understanding of neuro-oncological regulation, underscoring the nuanced interplay between neurological and oncological processes (termed as Cancer-Neuroscience). First, we elucidated how the nervous system accelerates tumor growth, metastasis, and the tumor microenvironment both directly and indirectly through the action of signaling molecules. Importantly, neural activity is also implicated in modulating the efficacy of therapeutic interventions, including immunotherapy. On the contrary, the nervous system potentially has a suppressive effect on tumorigenesis, further underscoring a dual-edged role of neurons in cancer progression. Consequently, targeting specific signaling molecules within neuro-oncological regulatory pathways could potentially suppress tumor development. Future research is poised to explore the intricate mechanisms governing neuro-tumor interactions more deeply, while concurrently refining treatment strategies for tumors by targeting the crosstalk between cancer and neurons.